ANALISIS MODEL SEBARAN BAHAN PENCEMAR Dl PERAIRAN SELAT NGUAN, BATAM - Sachoemar, Suhendar I; Purwanda, Andri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Analysis of the pollutant transport model was conducted to understand themagtitude, their pattern and spreading speed of the pollutant at Nguan narrowchannel of Batam. The RMA2 (Resource Management Associates) analysis wasemployed to solve those phenomena. The target analysis of the pollutant issuspended particulate matter (sediment), a rnost dominant pollutant matter withinthis area. The result shows that the spreading pollutant was strongly associatedwith the monsoonal system, current speed, tidal system and the pollutant source.The southward direction of sediment transport was inluenced by the northwestmonsoon and the tidal flood. While the northward direction was affected by thethe southeast monsoon and the ebb tide. The current speed was identified asmain factor causing the flushing out magnitude of the water mass at the channel, inwhich the flushing out in the northwest monsoon was faster than that in the southeastmonsoon. As consequence, the water resident time was to be short, the pollutantwas easily to be cleaned out and as the result, the water quality within the channelwas to be excellent.